ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEJADIAN READMISI PADA PASIEN BPJS RAWAT INAP DI RSUP PERSAHABATAN - Pratiwi, Annisa Endah (Journal of Health Service Management, 2024)
ABSTRACT Background: Readmission is often regarded as an indicator of poor quality of care and is used to assess hospital performance. The readmission rate also reflects the hospital's response to the shift in payment systems following the implementation of BPJS as Indonesia's national health insurance. In 2023, RSUP Persahabatan reported a readmission rate index (RaR) of 12%. Objectives: This study aims to analyze the factors affecting readmission events among BPJS inpatients in 2023 at RSUP Persahabatan and to formulate strategies to reduce the readmission rate. Methods: This research employed a mixed-methods sequential explanatory design. Quantitative analysis was conducted on BPJS inpatient records from 2023 for patients aged 18 years or older who experienced readmission. Data sources included BPJS claims and electronic medical records. Qualitative analysis was conducted through focus group discussions. Quantitative data were analyzed using chi-square tests and multivariate logistic regression. Results: Significant relationships were found between readmission and variables such as comorbidity, Charlson Comorbidity Index (CCI), severity level, polypharmacy, length of stay, admission through the emergency department, history of ED visits and inpatient care, and alignment with the clinical pathway (p<0.05). Patients who did not receive care aligned with the clinical pathway had a five-fold increased risk of readmission. Strategies to reduce readmission involve three stages: during admission, while the patient is still in care, and after discharge. Conclusions: Readmission at RSUP Persahabatan is prevalent among chronic patients with severe comorbidities. Adherence to the clinical pathway is crucial for reducing readmission rates and is a reflection of service quality. Efforts to reduce readmission must involve management and clinicians, requiring the integration of technology and a commitment to comprehensive patient care. Keywords: Readmission, reducing readmission, service quality.